TEACHING IDENTITIES AND THE DEVELOPMENT OF PRESCHOOL AND ELEMENTARY STUDENTS DURING REMOTE TEACHING - Maria de Lourdes Ramos da Silva; Giovanna Avalone Rovai (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
This article aims to reflect on the relationship between teaching identities and the socioaffective and cognitive development of preschoolers and elementary students during the emergency remote teaching imposed by Covid-19 in 2020. Therefore, descriptive qualitative study was conducted using semi-structured interviews with teachers who experienced teachinglearning processes and child development throughout this period. Results emphasize the importance of a close relationship between students and teachers and stress how much social interactions and activities that were planned to promote socialization are important during school life.